2018
DOI: 10.1155/2018/4572893
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidins Extracted from Lotus Seedpod Ameliorate Amyloid‐β‐Induced Toxicity in Rat Pheochromocytoma Cells

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease, which is characterized by extracellular senile plaque deposits, intracellular neurofibrillary tangles, and neuronal apoptosis. Amyloid-β (Aβ) plays a critical role in AD that may cause oxidative stress and downregulation of CREB/BDNF signaling. Anti-Aβ effect has been discussed as a potential therapeutic strategy for AD. This study aimed to identify the amelioration of procyanidins extracted from lotus seedpod (LSPC) on Aβ-induced damage with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Meanwhile, a significant decrease in the abilities of spatial learning and memory was observed through MWM test in Aβ‐induced mice, while Q3G administration improved memory. Consistent with our previous study, [ 31 ] we also observed supplement with Q3G restored hippocampal CREB activity and BDNF levels, which were pivoted in the synaptic plasticity and tightly related with memory developing. [ 49 ] Taken together, our findings indicated that Q3G might ameliorate cognitive impairment and trigger a beneficial effect on synaptic plasticity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, a significant decrease in the abilities of spatial learning and memory was observed through MWM test in Aβ‐induced mice, while Q3G administration improved memory. Consistent with our previous study, [ 31 ] we also observed supplement with Q3G restored hippocampal CREB activity and BDNF levels, which were pivoted in the synaptic plasticity and tightly related with memory developing. [ 49 ] Taken together, our findings indicated that Q3G might ameliorate cognitive impairment and trigger a beneficial effect on synaptic plasticity.…”
Section: Discussionsupporting
confidence: 93%
“…[28,29] In our previous study, LSPC exhibited the improvement of cognitive dysfunction and memory loss in the aged rats [30] and anti-A toxicity effects of LSPC on rat pheochromocytoma cells. [31] Through LC-MS/MS, we found that quercetin-3-O-glucuronide (Q3G) in LSPC was a primary metabolite in the brain. Quercetin was proved the effects of anti-Alzheimer, anti-diabetic, and anti-obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Procyanidins upregulate the SIRT1 that stimulates CREB (cAMP response element-binding), which acts as a molecular switch from short to long term memory ( Zhao et al, 2019 ). A new investigation has illustrated that procyanidins maintain cellular morphology and protect it from deformation and decrease apoptosis rates in PC12 cells induced by Aβ 25–35 ( Huang et al, 2018 ).…”
Section: Sirt1 and Sirt2 In Alzheimer’s Diseasementioning
confidence: 99%
“…FoxO1 promotes glucose production in the liver along with the conversion of carbohydrate oxidation to lipid oxidation in fasting muscle [ 30 ]. In the fasting state, hepatic FoxOs [ 31 ] are activated owing to the decrease in Akt levels [ 32 ]. FoxOs mediates glucose metabolism by converting glucose to acetate for oxidation or to fatty acids [ 33 ].…”
Section: Differential Roles Of Akt/foxos Axis In Metabolic- and Non-metabolic Organsmentioning
confidence: 99%
“…We previously reported that Akt-induced FoxO1 phosphorylation was reduced in the livers of aged rats, whereas it was increased in the kidney [ 65 ]. Different trends of changes in the Akt/FoxOs axis in metabolic and non-metabolic organs during aging are shown in Table 1 [ 31 , 32 , 60 - 62 , 66 - 73 ].…”
Section: Differential Roles Of Akt/foxos Axis In Metabolic- and Non-metabolic Organsmentioning
confidence: 99%